Pengaruh Dosis Pupuk Kotoran Ternak Ayam Terhadap Pertumbuhan dan Produksi Rumput Brachiaria humidicola pada Pemotongan Pertama - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
The aims of this research were to determine the effect dosage of chicken manure and want to know the dosage of chicken manure that give the best result for growth and production of Brachiaria humidicola.